Qualitative research methods - Hennink, Monique M.; Hutter, Inge.; Bailey, Ajay 1979-. (Thousand Oaks, Calif. SAGE, 2011)
"The book is based on the authors' highly successful multidisciplinary qualitative methods workshops, which have been conducted for over a decade. They introduce a 'qualitative research cycle' that leads students through the selection of appropriate methods, the collection of data, and the transformation of findings into a finished project. The book provides a clear explanation of the nature of qualitative research and its key concepts"--P. [4] of cover.
Keywords: Social sciences -- Research; Qualitative research